Small molecule screening as an approach to encounter inefficient myelin repair. (December 2021) - Manousi, Anastasia; Küry, Patrick
Abstract: While current multiple sclerosis therapies are focused on immunomodulation, thereby slowing down disease progression, scientific interest has nowadays been shifted toward regenerative therapies aiming at reversing already existing deficits. The application of chemical compounds was proven to be valuable for the understanding of oligodendrogenesis and for exposing mechanisms that can boost remyelination. However, sufficient myelin repair has not been achieved yet, thus underscoring the need for more studies toward this unmet clinical goal. In this regard, many research groups have significantly contributed to the field via developing compound screening approaches or using single substances. We, here, present an overview of recent studies addressing the identification of myelin repair drugs and provide insights into technical aspects and identified substances.